The Pressure of Religious Idealism and the Mental Health of Islamic Education Students: A Phenomenological Study in the Social Media Era - Muhammad Khalilurrahman; Mahsa Ramadhan Pratama; Adrian Sondak; Surawan Surawan (Muhammadiyah University of Makassar, 2026)
The development of social media has created a new space in the formation of religious identity among young people, including students of Islamic Religious Education (PAI). In the digital space, religiosity is not only practiced personally but also displayed as a representation of identity that can be observed and evaluated by the public. This condition has the potential to create pressure for religious ideality, especially for PAI students who are often perceived as moral representatives and symbols of religiosity in society. This study aims to explore the subjective experiences of PAI students in facing the pressure of religious ideality formed through social media dynamics and its implications for mental health. This study uses a qualitative approach with the Interpretative Phenomenological Analysis (IPA) method. The research participants consisted of five active students from the Islamic Religious Education Study Program, class of 2023, selected through purposive sampling techniques.Data were collected through semi-structured in-depth interviews, limited observation, and documentation. Data analysis was conducted thematically through the stages of data reduction, data presentation, and drawing conclusions to understand the meaning of participants' religious experiences. The results of the study indicate that the pressure of religious idealism on Islamic education students arises through three main dimensions: the demand to be a religious role model, the obligation to maintain a religious image in social interactions and digital media, and fear of social judgment. This pressure produces psychological impacts such as moral anxiety, overthinking, religious identity conflicts, and mental fatigue. However, some students are able to manage this pressure through the internalization of religious values and spiritual practices that function as coping mechanisms. In this context, social media plays an ambivalent role as a source of religious inspiration as well as a space for social comparison that can reinforce religious pressure. The findings of this study affirm that the pressure of religious idealism on PAI students is a phenomenon influenced by the interaction between personal religiosity, social expectations, and digital culture.